Biochemistry of very-long-chain and long-chain ceramides in cystic fibrosis and other diseases: The importance of side chain - Garić, Dušan; De Sanctis, Juan B; Shah, Juhi; Dumut, Daciana Catalina; Radzioch, Danuta (Progress in lipid research, 2019)
Ceramides, the principal building blocks of all sphingolipids, have attracted the attention of many scientists around the world interested in developing treatments for cystic fibrosis, the most common genetic disease of Caucasians. Many years of fruitful research in this field have produced some fundamentally important, yet controversial results. Here, we aimed to summarize the current knowledge on the role of long- and very-long- chain ceramides, the most abundant species of ceramides in animal cells, in cystic fibrosis and other diseases. We also aim to explain the importance of the length of their side chain in the context of stability of transmembrane proteins through a concise synthesis of their biophysical chemistry, cell biology, and physiology. This review also addresses several remaining riddles in this field. Finally, we discuss the technical challenges associated with the analysis and quantification of ceramides. We provide the evaluation of the antibodies used for ceramide quantification and we demonstrate their lack of specificity. Results and discussion presented here will be of interest to anyone studying these enigmatic lipids.
Keywords: Ceramides; Asthma; zvířata; Humans; ceramidy; Cystic Fibrosis; lidé; cystická fibróza; bronchiální astma; Animals